Development of student activities sheet based on apos theory to understand the concept of Riemann sum - Maya Saftari; Darmawijoyo Darmawijoyo; Yusuf Hartono (Math Didactic: Jurnal Pendidikan Matematika, 2020)
This research method used is design research type development study. This research develops teaching materials in the form of student activity sheets about the Riemann sum based on APOS theory that is valid, practical, and has a potential effect in mathematics learning. Research utilizing Microsoft Excel software. Development of teaching materials through stages, preliminary study dan formative study. The preliminary stage included preparation and design, the formative study stage included Self Evaluation, Expert Reviews, One to One, Small Group and Field Test. The validity of teaching materials was stated by two experts (expert review), two peers and three students (one-to-one). The practicality of instructional materials was seen from the results of small group activities. Based on the result of field test, it was found that the use of LAM teaching materials based on the APOS theory developed had a potential effect on the comprehension ability of mathematics concept especially in Riemann sum concept, From the result of the test, the percentage of concept comprehension was above 61.00%. this illustrates all of indicators of understanding students' mathematical concepts were good.